2010
DOI: 10.3233/isb-2010-0435
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Approach for Identification of Epitopes in Dengue Virus Envelope Protein: A Step Towards Designing a Universal Dengue Vaccine Targeting Endemic Regions

Abstract: A major problem in designing vaccine for the dengue virus has been the high antigenic variability in the envelope protein of different virus strains. In this study, a computational approach was adopted to identify a multi-epitope vaccine candidate against dengue virus that may be suitable for large populations in the dengue-endemic regions. Different bioinformatics tools were exploited that helped the identification of a conserved immunological hot-spot in the dengue envelope protein. The tools also rendered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…It was found that YYYELYPTM interacts with 19 HLA-A, HLA-B and HLA-C alleles in total. Analyzing similar data from other study showed this specific high affinity binding is absolutely desired because the efficiency of an epitope vaccine greatly relies on the precise interaction between epitope and HLA alleles (Chakraborty et al, 2010). This specific high affinity binding is absolutely desired because the efficiency of an epitope vaccine greatly relies on the precise interaction between epitope and HLA alleles.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It was found that YYYELYPTM interacts with 19 HLA-A, HLA-B and HLA-C alleles in total. Analyzing similar data from other study showed this specific high affinity binding is absolutely desired because the efficiency of an epitope vaccine greatly relies on the precise interaction between epitope and HLA alleles (Chakraborty et al, 2010). This specific high affinity binding is absolutely desired because the efficiency of an epitope vaccine greatly relies on the precise interaction between epitope and HLA alleles.…”
Section: Discussionmentioning
confidence: 66%
“…But novel vaccine approaches like DNA vaccines and epitope based vaccines have the potential to overcome these barriers for these vaccines can create more effective, specific, strong and long lasting immune response with minimal structure and devoid of all the undesired effects (Arnon, 2006). On top of that neutralizing peptide based vaccine design has been successfully suggested by using in silico approach against rhinovirus (Lapelosa et al, 2009) dengue virus (Chakraborty et al, 2010), Human coronaviruses (Sharmin and Islam, 2014), Hepatitis C virus (Idrees and Ashfaq, 2013), Saint Louis encephalitis virus (Hasan et al, 2013). Such studies regarding those viruses established immunoinformatics study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using various bioinformatics tools, we can design peptide vaccines based on a neutralizing epitope. For example, in silico design of an epitope-based vaccine against human immunodeficiency virus 23,24 , coronavirus 25 , dengue virus 26 , and Saint Louis encephalitis virus 27 has already been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In L1 protein, L1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (EATVYLPPVPVSKVV-type16), L1 408-421 (PPPGGTLEDTYRFV-type16) and L1 404-417 (NFGVPPPPTTSLVD-type 18) epitopes had the best B cell epitope identification scores. For L2 protein, L2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (KQSGTCPPDVVPKV-type18), L2 100-113 (PSDPSIVSLVEETS-type16), L2 94-107 (EPVGPTDPSIVTLI-type18) and L2 [57][58][59][60][61][62][63][64][65][66][67][68][69][70] (GLGIGTGSGTGGRT-type16) epitopes showed the highest epitope identification score between their own protein sequences.…”
mentioning
confidence: 99%
“…, A:Y47, A:V50, A:F51, A:I52, A:I54, A:P55, A:L56, A:F57, A:V58, A:I59, A:H60, A:T61, A:H62, AHigher rates show better quality of epitope identificationKhairkhah et al 2018), dengue virus(Chakraborty et al 2010) and coronavirus(Oany et al 2014). …”
mentioning
confidence: 99%